The rise of the WZIĄĆ (TAKE) Serial Verb Construction in Polish - Andrason, Alexander; Gębka-Wolak, Małgorzata; Moroz, Andrzej (Stellenbosch Papers in Linguistics Plus, 2022)
The present study is dedicated to the emergence of an asymmetrical serial verb construction (SVC) with the verb wziąć in Polish. By making use of a dynamic prototype-driven approach to linguistic categorization and by reviewing the historical corpora that range from the first Old Polish texts in the 14th c. until the end of the New Polish period in 1939, the authors conclude that the wziąć SVC has resulted from the fusion of the original conjunctively coordinated (CC) clauses. Although two types of clause-fusion mechanisms have operated during the grammaticalization of the wziąć SVCs, their contribution to this process has been dissimilar. The evolution from the syndetic CC with the coordinator i to the wziąć SVC via a pseudo-coordinated (PC) stage (i.e., the wziąć-i PC) has constituted a faster and stronger drift, while the more direct evolution originating in the asyndetic CC with wziąć has been slower and less pervasive.